If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4x + 25) + -3(4x + -1) = 5(4x + -7) Reorder the terms: 4(25 + 4x) + -3(4x + -1) = 5(4x + -7) (25 * 4 + 4x * 4) + -3(4x + -1) = 5(4x + -7) (100 + 16x) + -3(4x + -1) = 5(4x + -7) Reorder the terms: 100 + 16x + -3(-1 + 4x) = 5(4x + -7) 100 + 16x + (-1 * -3 + 4x * -3) = 5(4x + -7) 100 + 16x + (3 + -12x) = 5(4x + -7) Reorder the terms: 100 + 3 + 16x + -12x = 5(4x + -7) Combine like terms: 100 + 3 = 103 103 + 16x + -12x = 5(4x + -7) Combine like terms: 16x + -12x = 4x 103 + 4x = 5(4x + -7) Reorder the terms: 103 + 4x = 5(-7 + 4x) 103 + 4x = (-7 * 5 + 4x * 5) 103 + 4x = (-35 + 20x) Solving 103 + 4x = -35 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 103 + 4x + -20x = -35 + 20x + -20x Combine like terms: 4x + -20x = -16x 103 + -16x = -35 + 20x + -20x Combine like terms: 20x + -20x = 0 103 + -16x = -35 + 0 103 + -16x = -35 Add '-103' to each side of the equation. 103 + -103 + -16x = -35 + -103 Combine like terms: 103 + -103 = 0 0 + -16x = -35 + -103 -16x = -35 + -103 Combine like terms: -35 + -103 = -138 -16x = -138 Divide each side by '-16'. x = 8.625 Simplifying x = 8.625
| 2x-(5-(3x+4))=x-5 | | (5c-4c)+(c-3c)= | | 5(12-3x)+x=3(-2x+4) | | x=(x+1)*0.62 | | 0=ln(6x) | | 11=-16+7w | | 79-2x=9-9x | | 4x+9=-54+11x | | b+2=11-b/4 | | 1+8x=-6+x | | 0.4+(0.35e)= | | y=16*6+3 | | -46+8r=8(r-5) | | mn-4m-5n+20= | | y=16*9+9 | | u+9=v | | 4x+22=11x-8 | | 4x+12x=-29+x | | 7d+3d+6d+7=6d | | -8+12=-20 | | 6x-18=3x+11 | | 2x+y=8x+4yforx | | v-3/8=v/3 | | -4x+5=6x | | 36*x^2+4y^2-8y+9z^2-32=0 | | n+9/7=n+3/4 | | 2x+y=8x+4y | | 3(2x-5)+6(3x-1)= | | -10x+5+8x=17 | | 112=2(4+w) | | 9x+8-5x-3=6x+13 | | 5x-4x+3x=32 |